1981
DOI: 10.1056/nejm198107163050302
|View full text |Cite
|
Sign up to set email alerts
|

Children with Normal-Variant Short Stature: Treatment with Human Growth Hormone for Six Months

Abstract: Children with normal-variant short stature can be classified into four subgroups by measuring their anabolic and growth reactions to a 10-day course of human growth hormone. In Subgroup 1 there is no anabolic or growth reaction; in Subgroup 2 there is a weak anabolic reaction but no growth; Subgroups 3 and 4 have both reactions but Subgroup 4 is more responsive than Subgroup 3. We monitored growth rate and plasma immunoreactive somatomedin C concentrations in four to six children from each subgroup (age range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(74 citation statements)
references
References 12 publications
4
69
0
1
Order By: Relevance
“…The diagnosis of 'syndrome of bioinactive GH' has often been discussed and suggested in short children with the phenotype resembling isolated GHD with normal or even slightly elevated basal GH levels, low IGF1 concentration, and normal catch-up growth on GH replacement therapy. Short stature associated with bioinactive GH was first described by Kowarski et al (12) while additional cases were reported in the 1980s on clinical basis (13,14,15,16,17). Takahashi et al (18) described a heterozygous point mutation in the GH1 gene (D112G) found in a Japanese patient with short stature.…”
Section: Introductionmentioning
confidence: 98%
“…The diagnosis of 'syndrome of bioinactive GH' has often been discussed and suggested in short children with the phenotype resembling isolated GHD with normal or even slightly elevated basal GH levels, low IGF1 concentration, and normal catch-up growth on GH replacement therapy. Short stature associated with bioinactive GH was first described by Kowarski et al (12) while additional cases were reported in the 1980s on clinical basis (13,14,15,16,17). Takahashi et al (18) described a heterozygous point mutation in the GH1 gene (D112G) found in a Japanese patient with short stature.…”
Section: Introductionmentioning
confidence: 98%
“…There have been several reports that bioinactive GH may be responsible for growth retardation (1)(2)(3)(4)(5)(6)(7)(8). However, the molecular basis of bioinactive GH has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for diagnosing deficiency of GH and other pituitary hormones have been given before (4). These criteria included a mean peak immunoreactive GH level less than 4 ng/ml during four pharmacologic provocative tests (L-dopa or glucagon), as well as a plasma level of SmC less than 0.30 unit/ml.…”
Section: Methodsmentioning
confidence: 99%
“…All children had four plasma SmC determinations at 6-wk intervals. Those with average SmC below the lower 2.5 percentile tolerance limit for chronologic age ("hyposomatomedinemic children") as defined during phase 1, then received the clinical evaluation for growth retardation described previously (4). Two or more provocative tests were done with dopa or glucagon (7) (if the peak value in the first two provocative tests averaged >12 ng/ml?…”
Section: Methodsmentioning
confidence: 99%